Effect of subinhibitory concentration of chlorhexidine on Streptococcus agalactiae virulence factor expression - Galice, Denize Maria; Bonacorsi, Cibele; Gomes Soares, Veronica Cristina; Goncalves Raddi, Maria Stella; da Fonseca, Luiz Marcos (Elsevier B.V., 2006)
The aim of the present study was to investigate the effect of chlorhexidine at subinhibitory concentration (50% minimal inhibitory concentration (MIC)) on the growth, cytolysin expression and phagocytosis of Streptococcus agalactiae ATCC 13813. Bacterial growth with and without chlorhexidine treatment was monitored by turbidity measurements, and exocytolysins were estimated by neutral red uptake assay by the McCoy cell line. The phagocytic process was evaluated using luminol-enhanced chemiluminescence to follow the respiratory burst of polymorphonuclear neutrophils exposed to bacteria. Chlorhexidine-treated culture did not exhibit a detectable decrease in cell growth, and no statistically significant reduction in the respiratory burst of polymorphonuclear neutrophils was observed. However, growth in the presence of chlorhexidine resulted in a significant reduction of S. agalactiae exocytolysins. Although 50% MIC of chlorhexidine did not interfere with S. agalactiae growth and phagocytosis, the knowledge that this concentration was still able to alter some bacterial virulence parameters may be useful in its therapeutic applications. (c) 2006 Elsevier B.V. and the International Society of Chemotherapy. All rights reserved.
Keywords: chlorhexidine; Streptococcus agalactiae; subinhibitory concentration